IMPLEMENTATION OF INTELLECTUAL PROPERTY RIGHTS WAQF IN THE URBAN SOCIETY OF MEDAN BASED ON MAQASID SHARIAH - Rahmadany, Rahmadany; Pagar, Pagar; Khoiri, Nispul; Uwem, Imoh Emmanuel (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
This study aimed to see the implementation of intellectual property rights (IPR) waqf in urban society from the Perspective of Maqasid Shariah. This research applied a qualitative approach to depict social phenomena and processes in implementing Intellectual Property Rights Waqf in Medan urban communities. The qualitative approach allows researchers to gain deep insight into people's views, attitudes, and understanding of waqf and intellectual property rights. The data collection techniques used were interviews and documentation. The findings show that the implementation of IPR waqf in the urban society of Medan City, from the perspective of Maqasid Shariah, holds great potential for societal development and the promotion of knowledge and innovation. However, clear regulations and guidelines that address the specific challenges of IPR waqf must be established to facilitate its successful execution. Through collaboration and a comprehensive approach, the integration of IPR assets into the waqf framework can bring significant social and economic benefits to the urban society of Medan City. Despite the challenges faced, the implementation of IPR waqf in Medan City holds immense potential for the development and growth of the urban society.